PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT ANTAM TBK UBPP LOGAM MULIA - Dwi Paryanti; Rasmansyah (Jurnal Ekonomi dan Industri, 2020)
This study aims to determine the role of competence and motivation in improving the performance of employees of PT. Antam Tbk UBPP Logam Mulia. The number of samples taken in this study were 102 respondents. Based on the results of hypothesis testing shows that competence and motivation have a positive and significant effect on employee performance at PT. Antam Tbk UBPP Logam Mulia.